STRATEGIC HEALTH RISK COMMUNICATION OF HIV/AIDS ON TWITTER ACCOUNT @hayVeeID (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2022)
This research defines the utilization of the Twitter account @hayVeeID as a strategic communication for health risk communication associated with HIV/AIDS. From year to year, the case of HIV is sadly still increasing. The age range that becomes the majority of the people living with HIV is 20 – 24 Years and 25 – 49 Years. Hence, it is necessary to see the other approach to communicating an infectious disease. The UK's Expert and NGOs propose that the government make online sex education because they are shy about discussing and asking questions if sex education is done in public. Since one of the causes of this infectious disease happens through sexual intercourse and sex education in Indonesia is still taboo, hayVee adapts this online campaign to reduce the number of cases and stigma. This study identifies whether the Twitter account of @hayVeeID can be used as a strategic communication for health risk communication and illustrates the usage of that Twitter account. Using the qualitative approach with an instrumental case study method shows that several aspects of strategic communication need to be improved, such as measurement and the time-bound to achieve their targets. In addition, the social media account of @hayVeeID can be used as well as strategic communication to alter the audience's cognitive, affective, and behavioral components. This finding follows the aspects of attitude change in risk communication. To cite this article (7th APA style): Kusuma, R. A. P., & Mulyasari, F. (2022). Strategic health risk communication of HIV/AIDS on twitter account @hayVeeID. Journal Communication Spectrum: Capturing New Perspectives in Communication 12(2), 124-134. https://doi.org/10.36782/jcs.v12i2.2278